An extension of Darbo's theorem and its application to existence of solution for a system of integral equations. Issue 1 (1st January 2019) - Banaei, Shahram
Abstract: In this paper, we extend Darbo's fixed point theorem in Banach space via the concept of the class of operators O ( f ;.) and obtain a tripled fixed point theorem. The main tool applied in our investigation is the technique of measures of noncompactness. Finally, as an application of our obtained results, we analyze the existence of solutions for a system of integral equations.